3D Metallic Ti@Ni0.85Se with Triple Hierarchy as High‐Efficiency Electrocatalyst for Overall Water Splitting. Issue 10 (9th April 2019) - Yang, Chunming; Zhang, Junjun; Gao, Guimei; Liu, Darui; Liu, Ruiping; Fan, Ruicheng; Gan, Shucai; Wang, Ying; Wang, Yongwang
Abstract: In this study, Ti@Ni0.85 Se electrodes with a triple hierarchy architecture were designed, and their applications in electrocatalytic water splitting were studied. The 3D electrode is comprised of three types of structures including the bottom square Ti mesh structure as the conductive substrate, a vertical and uniform Ni0.85 Se nanosheet arrays structure in the intermediate section, and the topmost Ni0.85 Se flower structure. This triple hierarchy architecture is binder‐free, conductive, and has a particular feature of enlarged surface areas, exposing more active sites, promoting mass‐ and charge‐transfer, and accelerating dissipation of gases generated during water electrolysis. Moreover, DFT calculations confirmed that the Ni0.85 Se possesses metallic character, which further promotes the charge transfer of the electrocatalyst. Benefiting from this special structure and metallic character, the electrode displays a superior activity of 10 mA cm −2 at 120 mV hydrogen evolution reaction overpotential and 30 mA cm −2 at 270 mV oxygen evolution reaction overpotential. By using this electrode as a bifunctional electrocatalyst, an alkali electrolyzer affords a water splitting current of 10 mA cm −2 at a cell voltage of 1.66 V. Abstract : Metallic Ni0.85 Se directly grown on Ti mesh with a triple hierarchy architecture is reported as a bifunctional catalyst with high activity toward oxygen evolution and hydrogen evolution reactions in alkaline media. The unique triple hierarchy architecture offers significantly enlarged reactive surface area and the metallic behavior of Ni0.85 Se promotes the electron transportation for water splitting.